MODEL PENGEMBANGAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH BERBASIS ISLAMIC LEADERSHIP - Oman Fathurohman; Rifqi Fauzi; Wijoyo Wijoyo (Universitas Islam Bunga Bangsa Cirebon, 2022)
The managerial capacity of school principals constitutes the primary foundation in realizing effective, accountable, and quality governance of educational institutions. Field realities indicate that the majority of school principals, particularly in Islamic-based educational institutions, still face limitations in internalizing Islamic leadership values into their daily management practices. This study aims to examine, construct, and propose a model of school principal managerial competency development that organically integrates Islamic leadership principles as the spirit of every managerial dimension. The approach employed is qualitative with a library research method, relying on primary sources consisting of contemporary reference books and reputable national and international scientific journal articles. The analytical procedure was carried out through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the resulting model encompasses five main dimensions, namely: planning competency based on divine values, human resource management that emulates the character of the Prophet, development of an Islamic school climate, decision-making based on deliberation (musyawarah) and spiritual consultation (istikharah), as well as programmatic evaluation that is transparent and trustworthy (amanah). This model is expected to serve as a conceptual and practical reference for educational stakeholders in strengthening the capabilities of school principals in the era of national educational transformation.